Determinasi Pada Nilai Perusahaan - Nafisah, Sayyidati; Muniroh, Hetty (Universitas Sains dan Teknologi Komputer, 2024)
Company value can show how it performs in running the business. Company size, profitability, age and capital structure can have an effect on company value as proxied by PBV. This study was carried out in order to find out how company size, profitability, age and capital structure affect the value of Food and Baverage companies listed on the IDX during the 2019-2023 period. This study consists of the dependent variable company value, while the independent variables are company size, profitability, age and capital structure. The population used was 32 food and load businesses that were members of the BEI from 2019 to 2023. In this research, data was collected using a purposive sampling method. In this study sample, the research consisted of eleven companies with a total of fifty-five observations. The samples that have been collected are analyzed and processed using multiple linear regression tests. This study has findings that company size and age have an insignificant negative impact on company value, conversely the profitability variable has an insignificant impact on company value and capital structure has a positive impact on company value.